The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11420-013-9342-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Subsidence in Asymptomatic Patients After THR Using the Furlong Active HAP Stem

Abstract: Of the Furlong Active stems 61% subsided with initial weight bearing. Subsidence is higher in males, but no correlation has been found with age, stem diameter, morphology, osteopenia, or canal filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Published results on stem subsidence following cementless THA vary greatly with an average range of subsidence between 0.45 and 2.23 mm. 8,[29][30][31][32][33][34] Each cohort consisted of only patients that underwent THA with the DAA and the mean subsidence in our study was within the accepted range noted in the literature which suggests that approach does not affect subsidence outcomes. While excessive stem subsidence was not observed, there was a significant difference between cohorts with the less active MDS group experiencing greater subsidence than the SDD group (1.80 vs. 0.92mm, p < 0.001).…”
Section: Discussionsupporting
confidence: 56%
“…Published results on stem subsidence following cementless THA vary greatly with an average range of subsidence between 0.45 and 2.23 mm. 8,[29][30][31][32][33][34] Each cohort consisted of only patients that underwent THA with the DAA and the mean subsidence in our study was within the accepted range noted in the literature which suggests that approach does not affect subsidence outcomes. While excessive stem subsidence was not observed, there was a significant difference between cohorts with the less active MDS group experiencing greater subsidence than the SDD group (1.80 vs. 0.92mm, p < 0.001).…”
Section: Discussionsupporting
confidence: 56%
“…Follow-up included a maximum of 5 postoperative radiographs: during hospital stay, 6 weeks, 6 months, 1 year and 2 years postoperatively. Subsidence was digitally measured in a standardised technique from the highest point of the greater and lesser trochanter to the most lateral point of the stem-shoulder according to Bieger et al (24) and Cordero-Ampuero et al (25). Therefore, a coordinate system was digitally included in every postoperative image on each hip.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have reported on the subsidence of cementless hip stems, with some suggesting an inferior performance of short stem designs compared to conventional stems [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This could be detrimental for implant survivorship, as several authors suggested a correlation of early stem subsidence with aseptic loosening [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%